Mapping the English Pronunciation Errors of Pignatelli Triputra University Students - Poniman Poniman; Melania Lulut Mariani; Muhammad Sirod (STAI Hubbulwathan Duri, 2025)
Accurate pronunciation is critical for effective oral communication in English. However, many English as a Foreign Language (EFL) learners continue to struggle with mispronunciations, resulting in frequent misunderstandings during conversation. This study focuses on identifying common pronunciation errors among university students to inform targeted instructional strategies. A descriptive quantitative method was utilized, involving 30 students from Pignatelli Triputra University (UPITRA). Participants completed a pronunciation test comprising 125 commonly used English words. The test aimed to measure pronunciation accuracy and categorize error types. The results revealed that pronunciation errors ranged between 11% and 20% across the sample. Errors occurred across all phoneme types, including consonants, vowels, and diphthongs. Analysis indicated three primary causes of these mispronunciations: reliance on incorrect pronunciation analogies, spelling-based pronunciation attempts, and interference from native language phonology. These findings underscore the persistent challenges EFL learners face with English pronunciation. The identified error patterns suggest that conventional teaching approaches may not sufficiently address specific phonological issues. The study highlights the need for focused pronunciation training programs that consider linguistic interference and learner assumptions. Implementing such targeted interventions could significantly improve students' spoken English proficiency and minimize communication barriers.